(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2021)
Annotation. The paper notes the role of digitalization in modern conditions, as well as its importance in the HR management system. It is substantiated that the use of digitalization in the HR management system is a prerequisite for ensuring the future competitiveness and investment attractiveness of an enterprise through its transformation from traditional to technological, i.e. from offline to online. It has been established that the digitalization strategy in the HR management system should contain not only the basic principles and directions, methods and means of achieving the strategic goals of the HR digitalization process, but also reflect the factors and conditions necessary for the implementation of this process. The paper outlines the goal, principles and directions of the digitalization strategy in the HR management system.